2021
DOI: 10.1186/s40463-021-00549-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of validated parent-reported questionnaires assessing swallowing dysfunction in otherwise healthy infants and toddlers

Abstract: Objectives There has been increasing interest in the management of oropharyngeal swallowing dysfunction (SwD). Its prevalence, particularly in otherwise healthy infants and toddlers (OHITs), is underappreciated. As the standard diagnostic tests are either invasive or scarce, valid parent-reported outcome (PRO) questionnaires could play a pivotal role in the understanding and managing SwD in this group. This article reviewed the literature on PRO questionnaires pertaining to SwD in OHITs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Ideally, a comprehensive clinimetric review will include use of the COnsensus-based Standards to the selection of health Measurement Instruments (COSMIN) methodology (19)(20)(21). Previous reviews regarding PROMs in feeding have been completed (22)(23)(24)(25)(26)(27), universally identifying that many existing PROMs do not have robust psychometric data, and that further work is required. Unfortunately, only 2 of these reviews formally used the COSMIN methodology (22,27), and none focused specifically on any particular domain for PFD, given most preceded the proposal of the consensus definition (1).…”
Section: What Is Newmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, a comprehensive clinimetric review will include use of the COnsensus-based Standards to the selection of health Measurement Instruments (COSMIN) methodology (19)(20)(21). Previous reviews regarding PROMs in feeding have been completed (22)(23)(24)(25)(26)(27), universally identifying that many existing PROMs do not have robust psychometric data, and that further work is required. Unfortunately, only 2 of these reviews formally used the COSMIN methodology (22,27), and none focused specifically on any particular domain for PFD, given most preceded the proposal of the consensus definition (1).…”
Section: What Is Newmentioning
confidence: 99%
“…Previous reviews regarding PROMs in feeding have been completed (22)(23)(24)(25)(26)(27), universally identifying that many existing PROMs do not have robust psychometric data, and that further work is required. Unfortunately, only 2 of these reviews formally used the COSMIN methodology (22,27), and none focused specifically on any particular domain for PFD, given most preceded the proposal of the consensus definition (1). This lack of information leaves clinicians without clear guidance as to which tools should be used in their clinical practice to inform the diagnostic process for PFD.…”
Section: What Is Newmentioning
confidence: 99%
“…In the pediatric population, parent reported questionnaires could provide unique insight. Examples of parent-reported dysphagia questionnaires include PEDI-EAT-10 and the Parent Reported Outcome Questionnaire for Swallow Dysfunction in Healthy Infants and Toddlers, amongst several others [10,11].…”
Section: Otolaryngologic Clinical Evaluation In a Patient With Dyspha...mentioning
confidence: 99%
“…A higher prevalence of swallowing difficulties has been reported for some genetic conditions, including CHARGE (Blake & Hudson, 2017) and Moebius syndromes (Renault et al., 2020) and Wolf–Hirshhorn syndrome (Sabbadini et al., 2002). Interestingly, a recent study reported an incidence of paediatric swallowing difficulties in 0.9% of children aged 3–17 years living in the United States (Baqays et al., 2021; Bhattacharyya, 2015). The expanding survival rate of preterm infants and newborns with multiple health issues and disabilities can explain the increasing interest in dysphagia (Harding et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although several instruments have been developed to assess swallowing and feeding, data on their validity and reliability are still missing (Baqays et al., 2021).…”
Section: Introductionmentioning
confidence: 99%